The efficacy of platelet-rich plasma in ankle disease: a systematic review and meta-analysis - Qixin Ding; Xu Wang; Yurong Liu; Yuefang Li; Di Zhang; Heling Wang; Shenhong Ma; Qiaohua Han; Weisheng Zhuang (Journal of Orthopaedic Surgery and Research)
Abstract Objective Ankle osteoarthritis is a debilitating condition that significantly impairs patients’ quality of life. Platelet-rich plasma has emerged as a novel cellular therapy in clinical practice. This study evaluates the clinical efficacy of platelet-rich plasma (PRP) after intervention in ankle disorders, so as to provide strong evidence in support of clinical treatment. Methods A comprehensive and systematic search of PubMed, the Cochrane Library, Embase and web of science databases was performed, and studies that met the requirements according to the inclusion criteria were analyzed using Review Manager and STATA version 14.0. Quality assessment was performed using the Cochrane Collaboration Risk of Bias 2.0 tool. The outcome indicators were the American Orthopaedic Foot and Ankle Society Rating Scale (AOFAS) and Visual Analog Scale (VAS) scores used to evaluate the efficacy of platelet-rich plasma. Results A total of 10 studies met the inclusion criteria. Regarding the AOFAS score, a meta-analysis that included five randomized controlled trials (each study extracted the score results at the last follow-up time) showed no statistically significant differences between the platelet-rich plasma intervention group and the control group, and there was a great deal of heterogeneity in the results, with subgroup analyses based on disease type. (Mean Difference = 4.14, 95% CI=-0.60-8.87, p = 0.09, I2 = 86%). Subgroup analysis showed a more significant effect in patients with talar cartilage injuries (Mean Difference = 8.66, 95%CI = 6.61–10.71, p < 0.00001, I2 = 0%). And the treatment effect of PRP remained effective in long-term follow-up (Mean Difference = 7.83, 95% CI = 5.57–10.09, p = 0.46, I2 = 0%). For VAS scores, PRP relieved patients’ pain (Standardized Mean Difference=-0.62, 95%CI=-1.13–0.10, p = 0.02, I2 = 77%) but showed a greater advantage in patients with cartilage injuries of the talus (Standardized Mean Difference=-1.24, 95%CI=-1.68–0.81, p < 0.00001, I2 = 0%). Subgroup analyses according to different disease types and different follow-up times showed that PRP had significant efficacy in talar cartilage injuries in both the short and long term. A meta-analysis of single-arm studies showed that PRP was helpful in improving patients’ pain before and after the intervention (Standardized Mean Difference = -1.76, 95% CI = -2.85 to -0.67, p = 0.002, I^2 = 87%).However, the high level of heterogeneity may be due to the large differences between the inclusion criteria of the single-arm studies. Conclusion More clinical studies are needed to further confirm the efficacy of platelet-rich plasma in ankle disorders, and the current study only suggests that platelet-rich plasma may be more effective in talus cartilage injuries than in other types of ankle disorders.